Karakteristik Antisipasi Analitik Siswa SMA Dalam Memecahkan Soal Integral - Erfan Yudianto (FKIP Universitas Jember, 2015)
In an accuracy required to solve problems. One way to help students achieve the accuracy that is by directing students on analytical anticipation. The purpose of this study was to look at the characteristics of analytic anticipation of students in solving integrals. This study, data were collected by the method of tests and interviews. Test form about the area polynomial of degree two. Interviews were conducted to class XII student who has received the integral material. Results of this study are (1) the students read about the more than 1 times, (2) students find things that are known and things that asked, (3) students to describe matter in detail, (4) students combine kritria-criteria which are known in the matter, (5) students can find the link between things that are asked and things are known, (6) the students do the problems carefully, and (7) the students consider other alternative answers.